Alarming Tuberculosis Rate Among People Who Inject Drugs in Vietnam. (8th November 2021) - Nagot, Nicolas; Hai, Vinh Vu; Dong, Thuy Thi Thu; Hai, Oanh Khuat Thi; Rapoud, Delphine; Hoang, Giang Thi; Quillet, Catherine; Minh, Khue Pham; Vallo, Roselyne; Nham, Thanh Tuyet Thi; Castellani, Joëlle; Feelemyer, Jonathan; et al.
Abstract: Background: The tuberculosis (TB) epidemic is not homogeneous in the general population but presents high-risk groups. People who inject drugs (PWID) are such a group. However, TB among PWID remains largely undocumented. Our goal was to assess the prevalence of TB and the risk factors associated with TB among PWID in Vietnam. Methods: We implemented a cross-sectional survey among 2 community-based cohorts of human immunodeficiency virus (HIV)-positive and HIV-negative PWID in Hai Phong. Participants were screened for TB using questions on TB symptoms. Those who reported any symptom were accompanied by peers to the TB clinic for chest x-ray. If the latter was abnormal, a sputum was collected to perform an Xpert MTB/RIF test. Results: A total of 885 PWID were screened for TB. For both cohorts, most PWID were male (>90.0%), with a median age of 42 years. Beside heroin injection, 52.5% of participants reported smoking methamphetamine, and 63.2% were on methadone. Among HIV-positive PWID (N = 451), 90.4% were on antiretroviral therapy and 81.6% had a viral load <1000 copies/mL. Using a complete-case analysis, the estimated TB prevalence was 2.3% (95% confidence interval [CI], 1.0–4.5) and 2.1% (95% CI, 0.8–4.2) among HIV-positive and HIV-negative people, respectively. Living as a couple, arrest over the past 6 months, homelessness, and smoking methamphetamine were independently associated with TB but not HIV infection. Conclusions: In the context of very large antiretroviral therapy coverage, this extremely high rate of TB among PWID requires urgent actions. Abstract : Although TB is poorly described among PWID, we report a conservative estimate of TB prevalence as high as 1.7% in Hai Phong, Vietnam. Smoking methamphetamine was independently associated with TB, but not HIV, likely due to high ART coverage.